The Influence of the Storytelling Methods Using Media Barrier Game Picture on the Speaking Ability of Children Aged 4-5 Years in Kindergarten - Gusti, Safira Inaya; Rahmadani, Ni Kadek Aris (Universitas Negeri Semarang, 2025)
The aim of this study is to determine the influence of image media barrier game using storytelling methods to improve the speaking skills of children aged 4-5 years. This study used a quantitative approach, namely a preexperimental research type with a one-group pretest-posttest design. The study population was 40 students at RA Melati. The sampling technique used was a descriptive qualitative technique purposive sampling, namely the technique of taking data source samples with certain considerations so that the samples selected are not random but are determined by the researcher. The data collection technique uses observation, questionnaire, assessment scale and documentation. Data analysis techniques using normality tests and linearity tests with hypothesis testing using paired sample T-Test, simple linear regression test, coefficient of determination.The results of the research from the t-test calculation obtained a calculated t value > t table, namely -16.229 and a ttable value = 1.684 df = 39 with a significance value of 0.000 <0.05. can be interpreted that there is a significant increase in the speaking ability of children aged 4-5 years after being given treatment with image barrier game media because the calculated t-value is outside the t-table value until Ho is rejected and Ha is accepted. The results of the data normality test showed a significance value of Asymp sig (2-tailed) of 0.136, which is greater than 0.05, so it is concluded that the distribution is normal. There is a difference in the average value (mean) of children's speaking ability before being given a pretest, namely 72.175 and after being given treatment, namely 101.950, resulting in an increase of 29.77%